Perkembangan kalus embriogenik sagu (Metroxylon sagu Rottb.) pada tiga sistem kultur in vitro Development of embryogenic callus of sago (Metroxylon sagu Rottb.) on three systems of in vitro culture - Pauline D KASI; . SUMARYONO (Menara Perkebunan, 2008)
Summary Embryogenic callus of sago (Metroxylon sagu Rottb.) has been grown on three systems of in vitro culture i.e. agar-solidified medium, liquid medium, and temporary immersion system (TIS) medium to observe and compare the development of embryogenic callus over one passage of six weeks.  A-half gram of embryogenic callus was cultured on a modified MS medium containing 10 mg/L   2,4-D and 0.1 mg/L kinetin. For histological studies, embryogenic callus was fixed in FAA and embedded in paraplast wax. Serial sections were stained with safranin 1% and observed microscopically. By the end of culture period, the development of embryogenic callus in TIS medium was relatively better than those of the other two media.  Fresh weight of callus in liquid medium and TIS increased by 6.5-fold, while on agar-solidified medium increased by 5.4-fold in six weeks.  About 40% of callus in liquid medium and TIS and 20% of callus on agar solidified medium have changed into somatic embryos at globular stage. Histology structure of embryogenic callus of the three systems of in vitro culture shows different pattern. On agar-solidified medium, secondary callus and friable embryogenic callus that consist of meristematic cells were formed. In contrast, more embryogenic cells were formed in liquid medium and TIS to support maturation process to somatic embryos. Therefore, temporary immersion system and liquid medium are recommended for maturation of embryogenic callus, whereas agar-solidified medium is for proliferation of embryogenic callus of sago.  Ringkasan Kalus embriogenik sagu (Metroxylon sagu Rottb.) telah ditumbuhkan pada tiga sistem kultur in vitro yaitu medium padat, medium cair, dan medium dengan sistem perendaman sesaat (SPS) untuk mempelajari dan mem-bandingkan perkembangan dari kalus embrio-genik selama periode enam minggu. Setengah gram kalus embriogenik dikulturkan pada medium MS modifikasi yang mengandung  2,4-D 10 mg/L dan kinetin 0,1 mg/L.  Untuk studi histologi, kalus embriogenik difiksasi dengan FAA dan embedding menggunakan lilin paraplast. Irisan diwarnai dengan safranin 1% dan diamati menggunakan mikroskop. Pada akhir periode kultur, pertumbuhan kalus pada medium dengan SPS lebih baik dibandingkan dengan medium cair dan padat. Bobot basah kalus pada  medium cair dan SPS meningkat 6,5 kali sedangkan pada medium padat meningkat 5,4 kali dalam waktu enam minggu. Sebanyak 40% kalus pada medium cair dan SPS serta 20% kalus pada medium padat berubah menjadi embrio somatik fase globuler. Struktur histologi kalus embriogenik pada ketiga jenis sistem kultur in vitro menunjukkan pola yang berbeda. Pada medium padat terjadi pembentukan kalus sekunder dan kalus embriogenik remah yang terdiri atas sel-sel meristematik. Sebaliknya pada medium cair dan SPS pembentukan sel embriogenik lebih banyak yang menunjang proses pendewasaan menjadi embrio somatik. Oleh karena itu, medium cair dan SPS direkomendasikan untuk pendewasaan kalus embriogenik, sedangkan medium padat untuk proliferasi kalus embriogenik sagu.